PERAN KEPALA MADRASAH IBTIDAIYAH MUHAMMADIYAH DALAM MEMBENTUK KEUNGGULAN MENUJU MADRASAH UNGGULAN MAGELANG - Ahwy Oktradiksa; Irham Nugroho (Universitas Muhammadiyah Semarang, 2015)
There are madrassas which indicates a superior madrassa madrassa in fact superior to those faced with the efficiency and effectiveness of management is still found many obstacles to realize as a madrasah that really excels. The research focused on the study of the role of headmaster in the form of superior madrassa. The formulation of the problem in general is